2013
DOI: 10.5051/jpis.2013.43.4.153
|View full text |Cite
|
Sign up to set email alerts
|

What is the effect of initial implant position on the crestal bone level in flap and flapless technique during healing period?

Abstract: PurposeThe level of the implant above the marginal bone and flap design have an effect on the bone resorption during the healing period. The aim of this study is to detect the relationship between the level of the implant at the implant placement and the bone level at the healing period in the mesial and distal side of implants placed with flapless (FL) and full-thickness flap (FT) methods.MethodsTwenty-two nonsubmerged implants were placed with the FL and FT technique. Periapical radiographs were taken of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
1
9
0
2
Order By: Relevance
“…Another study conducted by Al‐Juboori et al. () evaluated the effect of initial implant position on the crestal bone level in flap and flapless technique during healing period. Twenty‐two non‐submerged implants were placed with the flapless and flap technique with a follow‐up of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study conducted by Al‐Juboori et al. () evaluated the effect of initial implant position on the crestal bone level in flap and flapless technique during healing period. Twenty‐two non‐submerged implants were placed with the flapless and flap technique with a follow‐up of 12 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This rich vascularity provided a good defense mechanism against bacterial invasion (Al‐Juboori et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the etiological factors of marginal bone loss is the disruption of the periosteum and blood supply during flap elevation and placement of implant [17]. Some studies showed that less marginal bone loss was noticed when flapless technique is used as compared with full-thickness flap technique that showed more marginal bone loss during healing period [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%